PENERAPAN ASAS ITIKAD BAIK PADA PENGALIHAN HAK ATAS TANAH TERHADAP HARTA DEBITOR PAILIT : APPLICATION OF THE PRINCIPLE OF GOOD FAITH IN THE TRANSFER OF LAND RIGHTS TO THE PROPERTY OF A BANKRUPTCY DEBTOR - Putra, Nouval Rivaldi; Fachrurozi, Aal; Suryanti, Nyulistiowati; Yuanitasari, Deviana (LPPM Universitas Doktor Husni Ingratubun Papua, 2023)
Giving debt or credit by creditors in their position as individuals or legal entities to debtors is a common occurrence in social life. Nowadays, it is rare to find an entrepreneur who does not use debt facilities (loans or credit) in the form of short-term debt. The regulations in bankruptcy law initially gave authority to creditors holding collateral rights, to be able to execute without being affected by bankruptcy, PT Bringin Srikandi Finance took legal action to transfer the land rights of PT Panghegar Kana Legacy, which is now in bankruptcy, to the name of PT Bringin Srikandi Finance which is one of the creditors of PT Panghegar Kana Legacy. This research will examine the application of the principle of good faith in the transfer of land rights by creditors to the assets of bankrupt debtors. Through a normative juridical approach with analytical descriptive methods, it can be determined that this is an act against the law and does not respect the principle of good faith at all.